PEREMPUAN DAN PEMBELAAN: ANALISIS WACANA KRITIS SARA MILLS DALAM PLEDOI PUTRI CANDRAWATHI - Pratiwi, Septiana; Abrian, Rizky (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to analyze Putri Candrawathi's pledoi by borrowing Sara Mills' glasses. The source of the data in this article is obtained from youtube kompas.com, while the data is Putri Candrawathi's story about the Pledoi. The purpose of this research is to find out the position of the subject-object, listener (reader), and the image of women who often get bad grades in the eyes of society. This research is a qualitative descriptive research, because the results of this research are in the form of a description of the data obtained from material objects. The results of this study indicate that the positions of the subjects in this pledoi were taken at once by Putri Candrawathi because she was telling herself (the subject) and making herself an object. Meanwhile, for the listener-reader position, Putri Candrawathi invites readers through the mediation method.